Characterization of Weathered and Intact Limestone with FTIR Analysis in Batu Caves, Malaysia - Kambakhsh, Hamasa; Nik Daud, Nik Norsyahariati; Saifullah Inanch (International Journal of Integrated Engineering, 2024)
This paper explores the complex geological processes involved in the weathering of limestone in Batu Cave, Malaysia. Batu Cave is well-known for its formations that hold cultural and geological importance. Limestone, consisting mostly of calcium carbonate, experiences weathering processes that are impacted by environmental conditions, necessitating a thorough investigation. The study used Fourier-transform infrared spectroscopy (FTIR) to thoroughly analyse six limestone samples from Batu Cave. The FTIR analysis provides essential information on the mineral composition of limestone. Three key objectives guided our investigation: i) to discern the physical properties of both intact and weathered limestone, ii) to scrutinize the wave spectrum through FTIR analysis, and iii) to elucidate the intricate relationship between physical and chemical properties during the weathering process. The FTIR findings provide significant insights into the mineral compositions of weathered limestone in Batu Cave. Within the cave, feldspar, calcite, and dolomite were identified, while beyond the cave’s confines, distinct peaks indicated the presence of calcite, dolomite, clay minerals, and magnesium-rich chlorite. Noteworthy peaks at 3440.51 cm?¹ and 3746.26 cm?¹ confirmed the existence of clay minerals and chlorite, enriching our understanding of geological changes resulting from weathering. Overall, the FTIR analysis improves our understanding of Batu Cave’s geological past by revealing the intricate connections between limestone and environmental elements. The results highlight the susceptibility of limestone formations to weathering. The ramifications transcend mere scientific curiosity, underscoring the imperative for comprehensive conservation endeavours aimed at safeguarding this emblematic natural and cultural legacy for posterity.